Superquadrics objects representation for robot manipulation - Silva, Eliana Oliveira Costa (2016)
Superquadric are mathematically quite simple and have the ability to obtain a variety of shapes using low order parameterization. Furthermore they present closed-form equations and therefore can be used in the formulation of robotic movement planning problems, in particular in obstacle-avoidance and grasping constraints. In this paper we explore the modeling of objects using superquadrics. The classical nonlinear optimization problem for fitting shapes is extended by adding nonlinear constraints. The numerical results obtained by two different optimization methods are presented and a comparison of the volume of the superquadrics to the volume of simple ellipsoids is made.